Sun protection Provided by Regulation School Uniforms in Australian Schools: An Opportunity to Improve Personal Sun protection During Childhood. (18th August 2014) - Turner, Denise; Harrison, Simone L.
Abstract Childhood sun exposure is linked to excessive pigmented mole development and melanoma risk. Clothing provides a physical barrier, protecting skin from ultraviolet radiation (UVR). Extending sleeves to elbow length and shorts to knee length has been shown to significantly reduce mole acquisition in preschoolers from tropical Queensland. We used publicly available uniform images and guidelines from primary schools in Townsville (latitude 19.25°S, n = 43 schools), Cairns (16.87°S, n = 46) and the Atherton Tablelands (17.26°S, n = 23) in tropical Australia to objectively determine the body surface proportion covered by regulation school uniforms. Uniforms of nongovernment, large (≥800 students), urban, educationally advantaged schools with comprehensive sun protection policies covered more skin than those of government schools (63.2% vs 62.0%; P < 0.001), smaller schools (63.4% vs 62.3%; P = 0.009), rural (62.7% vs 61.9%; P = 0.002) and educationally disadvantaged schools (62.8% vs 62.3%; P < 0.001) with underdeveloped sun protection policies (62.8% vs 62.2%; P = 0.002). Overall, SunSmart and non‐SunSmart school uniforms covered identical body surface proportions (62.4%, P = 0.084). Although wearing regulation school uniforms is mandatory at most Australian primary schools, this opportunity to improve children's sun protection is largely overlooked. Recent evidence suggests that even encouraging minor alterations to school uniforms (e.g. slightly longer sleeves/dresses/skirts/shorts) to increase skin coverage may reduce mole acquisition and melanoma risk, especially in high‐risk populations.